2013
DOI: 10.1021/ma400088w
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Relaxation and Rheological Behavior of Supramolecular Polymeric Liquid

Abstract: A model self-complementary supramolecular polymer based on thymine and diamidopyridine triple hydrogen-bonding motifs has been synthesized, and its dielectric and rheological behavior has been investigated. The formation of supramolecular polymers has been unequivocally demonstrated by nuclear magnetic resonance, electrospray ionization mass spectrometry with traveling wave ion mobility separation, dielectric spectroscopy, and rheology. The dynamical behaviors of this associating polymer generally conform to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
40
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 67 publications
3
40
1
Order By: Relevance
“…49 A crossover from an intermediate to the terminal power law reported for shortchain polymers, polymeric liquids, or monoalcohols (ν 0.7 ) is an evidence of an additional slow supramolecular organization/dynamics. [23][24][25]42,50 In the present study, due to resolution limits of the PSG technique, we were not able to clearly observe the change of the frequency dependence of G ′ and G ′′ at modulus values lower than 1 MPa. However, the power law of the lowfrequency part of the mechanical loss shear spectra for amine (ν 0.85 ) and thiol (ν 0.93 ) shows that they display an intermediate behavior between the one reported for non-associating and associating liquids.…”
contrasting
confidence: 63%
See 1 more Smart Citation
“…49 A crossover from an intermediate to the terminal power law reported for shortchain polymers, polymeric liquids, or monoalcohols (ν 0.7 ) is an evidence of an additional slow supramolecular organization/dynamics. [23][24][25]42,50 In the present study, due to resolution limits of the PSG technique, we were not able to clearly observe the change of the frequency dependence of G ′ and G ′′ at modulus values lower than 1 MPa. However, the power law of the lowfrequency part of the mechanical loss shear spectra for amine (ν 0.85 ) and thiol (ν 0.93 ) shows that they display an intermediate behavior between the one reported for non-associating and associating liquids.…”
contrasting
confidence: 63%
“…[32][33][34][35][36][37][38][39] 27 The slow supramolecular mode has been mainly documented for monoalcohols but very little studied for other types of hydrogen bonding liquids. 42,43 However, supramolecular hydrogen bonding structures can potentially be created by halogens, amines, and perhaps thiols as well. Their effective strength is expected to decrease in the same order as the difference in electronegativity of the constituting atoms.…”
mentioning
confidence: 99%
“…This spectral feature is interpreted to originate from the same supramolecular structures responsible for the dielectric Debye process, and is identical to what is observed for short chain polymers. 21,22 Furthermore, it has been shown that also nuclear magnetic resonance, 17 dynamic light scattering, 3 and quasi-elastic neutron scattering 23 are sensitive to the Debye-process and similar results have been seen in mechanical studies of supramolecular polymers 1 and high temperature alcohols.…”
mentioning
confidence: 73%
“…Liquids forming supramolecular structures are currently receiving a great deal of attention. [1][2][3][4][5] In this Communication, we present shear-mechanical spectroscopy results on monohydroxy alcohols (i.e., alcohols containing only a single OH group). A monohydroxy alcohol is one of the simplest systems showing pronounced formation of supramolecular structures and has been studied intensively in the past mainly by dielectric spectroscopy (dating back 100 years), but also by xray and neutron scattering, and calorimetry (see recent extensive review by Böhmer et al 5 and earlier compilation of classical results (Sec.…”
mentioning
confidence: 99%
See 1 more Smart Citation